CONFRONTING WHITENESS IN SOCIAL WORK EDUCATION THROUGH RACIALIZED STUDENT ACTIVISM - Mbakogu, Ifeyinwa; Duhaney, Patrina; Ferrer, Ilyan; Lee, Edward (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2021)
In 2010, a group of racialized doctoral students at an elite university in Canada collectively mobilized against institutional racism within their school of social work. They insisted that their school confront the ways in which White supremacy was embedded within various policies and practices. These early initiatives led to the creation of the Racialized Students’ Network (RSN). Although the RSN has ended, it has produced a new generation of scholars who continue to interrogate Whiteness and White supremacy. It has also offered roadmaps through which newer generations of racialized social work scholars can advance anti-racist and decolonial feminist perspectives within postsecondary social work institutions in Canada. In this article, the authors, who are now tenure-track or tenured professors at Canadian universities, demonstrate the ways in which graduate student anti-racist activisms are a central avenue for confronting Whiteness and institutional racism. Through a collaborative autoethnographic methodology, this article draws from the authors’ personal experiences within the RSN, the group’s source documents, and their collective analysis on how the RSN has informed their ongoing activism. They discuss how their everyday experiences align with current anti-racist struggles and movements to shape their actions and responses in academe. The RSN Model of Racialized Students’ Activism is presented to demonstrate the collective processes the student activists explored to reflect and apply their intersecting identities to support racialized students and address systemic racism.